2000
DOI: 10.1093/oxfordjournals.bja.a013401
|View full text |Cite
|
Sign up to set email alerts
|

NOx- concentrations in the rat hippocampus and striatum have no direct relationship to anaesthesia induced by ketamine

Abstract: Using microdialysis, we have examined the effects of ketamine on concentrations of total nitric oxide oxidation products (NOx-) in the rat hippocampus and striatum in vivo to investigate the relationship between anaesthesia and NOx- production in the brain. Ketamine 25, 50 and 100 mg kg-1 i.p. increased NOx- concentrations to mean 125 (SD 13)%, 165 (11)% and 193 (13)% of basal, respectively, in the hippocampus and to 122 (12)%, 147 (7)% and 177 (14)% of basal in the striatum. Local perfusion with ketamine 50 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…12 In line with this view, neurochemical data demonstrated that application of L-NAME counteracted the increase of nitric oxide plasmatic concentrations that were produced by anesthetic ketamine in the rat hippocampus. 13 Although important differences in experimental settings exist between these studies and our findings, these results further support a role for nitric oxide on ketamine's effects.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…12 In line with this view, neurochemical data demonstrated that application of L-NAME counteracted the increase of nitric oxide plasmatic concentrations that were produced by anesthetic ketamine in the rat hippocampus. 13 Although important differences in experimental settings exist between these studies and our findings, these results further support a role for nitric oxide on ketamine's effects.…”
Section: Discussionsupporting
confidence: 75%
“…For instance, the nonselective nitric oxide synthase (NOS) inhibitor, N-nitro-L-arginine methylester (L-NAME), antagonized ketamineinduced analgesia 11 ; and the neuronal NOS inhibitor, 7-nitroindazole, conferred protection against ketamine-induced neurotoxicity in newborn rat forebrain culture. 12 A microdialysis study 13 has demonstrated that L-NAME counteracted the increase induced by anesthetic ketamine of nitric oxide oxidation products in the rat hippocampus. Finally, L-NAME was able to reverse recognition and spatial memory deficits produced by subanesthetic doses (3 mg/kg) of ketamine in rats.…”
Section: He Noncompetitive Antagonist Of the N-methyl-d-as-mentioning
confidence: 99%
“…the actual concentration or amount of nitric oxide products in the brain could not be measured because the rate of recovery of neurotransmitters in perfusate from the extracellular space into a dialyzing probe through the membrane is not predetermined. alternations in recovery or No release might have occurred throughout the study, and consistent increases were found in every experiment, as found in a previous investigation [25]; however, we could not explain the reason for stable intraday changes. in summary, Ket increased No release in the rat striatum.…”
Section: Discussionsupporting
confidence: 81%
“…on the other hand, PB decreases ach release in both the hippocampus and striatum [18]. although wu et al [25] explained the PB-induced decrease and Ket-induced increase in No release as a result of the change that occurs in ach release in both the hippocampus and striatum, the conclusions were tenuous, especially those related to the striatum.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation